Abilities of protocatechuic acid and its alkyl esters, ethyl and heptyl protocatechuates, to counteract UVB-induced oxidative injuries and photoaging in fibroblasts L929 cell line - Daré, Regina G.; Oliveira, Mariana M.; Truiti, Maria C.T.; Nakamura, Celso V.; Ximenes, Valdecir F. [UNESP]; Lautenschlager, Sueli O.S. (Elsevier, 2020)
Ultraviolet B (UVB) radiation triggers the activation of many reactive oxygen species (ROS)-sensitive signaling pathways, resulting in the induction of skin damage that can progress to premature skin aging with long-term exposure. Even after the cessation of UVB radiation, the activated photosensitizers can still cause cellular injury. Thus, the use of photoprotectors that inhibit or prevent intracellular ROS production during or after UV exposure is one alternative to counteract UV-induced oxidative damage. The present study investigated the photoprotective activity of protocatechuic acid (P0) and its alkyl esters ethyl protocatechuate (P2) and heptyl protocatechuate (P7) against UVB-induced damage in L929 fibroblasts by evaluating biomarkers of oxidative stress and photoaging. P0, P2 and P7 markedly increased cell viability after UVB exposure. This protective effect was related to the ability of these compounds to absorb UVB and restore cellular redox balance even 24 h after UVB exposure. P0, P2 and P7 also decreased oxidative damage to membrane lipids, mitochondrial membrane potential, and DNA. They also inhibited the nuclear translocation of NF-κB p65 and downregulated the expression of the photoaging-related proteins matrix metalloproteinases-1 and -9 and cyclooxygenase-2. As the lipophilicity of the P0 derivatives increased, their antioxidant potency increased, but more pronounced cytotoxic effects were also detected. In summary, P0 and P2 may be promising candidates for the prevention and treatment of UVB-induced skin photodamage and photoaging.
Keywords: Oxidative stress; Photoaging; Protocatechuic acid; Protocatechuic acid alkyl esters; UVB